1972
DOI: 10.1177/0310057x7200100207
|View full text |Cite
|
Sign up to set email alerts
|

Ornipressin (Por. 8) for Haemostatic Infiltration in Neurosurgery

Abstract: A double blind controlled trial was carried out on 100 neurosurgical patients. Ornipressin 0•2 IU Iml was compared with adrenaline 1 : 250,000. Ornipressin proved to be as effective as the control agent, and had little systemic effect. It is concluded that absence of arrhythmigenicity makes ornipressin preferable to adrenaline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Several reports appeared in the literature about 10 years ago which suggested that the infiltration of ornipressin satisfactorily reduced bleeding during surgery but few of these were controlled clinical trials (REA 1969, MCCAFFREY 1970, SHIELL 1971. However, in one double-blind trial, TORDA et al (1972) did show that ornipressin and adrenaline were equally efficient haemostatic agents during a variety of neurosurgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports appeared in the literature about 10 years ago which suggested that the infiltration of ornipressin satisfactorily reduced bleeding during surgery but few of these were controlled clinical trials (REA 1969, MCCAFFREY 1970, SHIELL 1971. However, in one double-blind trial, TORDA et al (1972) did show that ornipressin and adrenaline were equally efficient haemostatic agents during a variety of neurosurgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Effective cutaneous vasoconstriction may be observed at drug concentrations as low as 0.0001 IU mL –1 , and maximal vasoconstriction occurs at concentrations between 0.01 and 0.1 IU mL –1 , depending on interindividual variability. The local vasoconstrictor action of ornipressin is approximately equal to that of adrenaline [12–16]. Thus, ornipressin is used to produce local haemostasis to reduce blood loss and provide a bloodless surgical field.…”
Section: Introductionmentioning
confidence: 99%
“…The localized vasoconstrictor activity of ornipressin, when used topically or by infiltration, has been utilized in a wide range of surgical procedures. In general, most studies have shown that ornipressin is at least similar to adrenaline in its vasoconstrictor action and with fewer side effects [12–16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations